Contractual and procedural effects of non-exclusive jurisdiction agreements - CHAN, Darius (Institutional Knowledge at Singapore Management University, 2012)
In Orchard Capital I Ltd v Ravindra Kumar Jhunjhunwala, a respondent’s attempt to stay Singaporean proceedings on forum non conveniens grounds in favour of a non-exclusive jurisdiction (Hong Kong) was denied. In doing so, the Singapore Court of Appeal set out important principles concerning the legal effects of a non-exclusive jurisdiction agreement. This note makes a comparative analysis of the decision with English case law. It will be seen that the decision has taken a bold and firm step in a direction where English case law had previously tiptoed but still not fully embarked.